Growth response to dietary additions of bacillus subtilis from weaning to 230 pounds - J A Swanson; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1989)
Two hundred fifty-five pigs, weaned at 4 wk of age, were used in an experiment to compare the efficacy of Bacillus subtilis and antibiotics as growth promoters for swine from nursery to finishing. Treatments were a nonmedicated control; B. subtilis added at 5 x 105, 1 X 106, or 5 x 106 CFU/g feed; or antibiotics (50 g/ton carbadox during the nursery phase and 100 g/ton chlortetracycline in the growing and finishing phases). Average daily gain and average daily feed intake were greater for pigs fed antibiotics in the nursery and grower phases than for pigs fed diets containing no medication or diets containing B. subtilis. Feed to gain ratio was not affected by the addition of B. subtilis or antibiotics. In the finishing phase, feeding B. subtilis and antibiotic did not affect avg daily gain, avg daily feed intake, or feed to gain ratio. From weaning to market weight, avg daily gain and avg daily feed intake were greater for pigs fed antibiotics than pigs fed the other treatments. Our results indicate that at the levels used in this experiment, feeding B. subtilis is not as effective as feeding antibiotics to improve performance of nursery and growing pigs. Neither B. subtilis nor chlortetracycline affected the performance of finishing pigs.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Pig; Bacillus subtilis; Antibiotics; Growth performance